New approaches of weed management in soybean - Choudhary, V. K.; Kewat, M. L.; Singh, P. K. (Indian Farming, 2018)
During rainy season, congenial weather conditions favour weeds to germinate and establish and offers competition to the soybean, resulting 40-60% of loss in productivity. Weeds in soybean can be managed mechanically by low-cost hand tools or inter-row cultivation between 2 and 4 weeks after sowing. Cultural practices such as crop rotation, intercropping, stale seed bed, soil solarization, mulching, weed competitive crop cultivars etc. help in reducing weed problem. However, to combat with the compounded problems due to weeds chemicals weed management such as metribuzin, metolachlor, pendimethalin, imazethapyr, fenoxaprop, chlorimuron (PoE) and some ready mix such as imazethapyr + imazamox, propaquizafop + imazethapyr, fomesafen + fluazifop, acifluorfen+clodinafop was found effective and economical.